Do Cruzamento Ideológico de Sun Yat-Sen com Jiang Zemin - Martins, Marco António Gonçalves Barbas Batista (2011)
It’s interesting to analyze the theory of the Three Represents of Jiang Zemin and the Three Principles of the People of Sun Yat-sen in order to study the importance of the political power of China to understand the practical applications of both theories as a guiding ideology.